KONSEP OMNIBUS LAW DITINJAU DARI UNDANG UNDANG NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG UNDANGAN - Dhaniswara K. Harjono (to-ra, 2020)
All forms of regulatory constraints must be simplified, especially overlapping regulations that require reform and harmonization so that they do not hamper investment. For this reason, the Government will make laws with the concept of Omnibus Law, which is an umbrella act. However, the umbrella law is not known in Law No. 12 of 2011 which regulates the formation of legislation. so to be enacted, the Omnibus Law must obtain legitimacy from Law No. 12 of 2011. This study uses a normative type of research with analytical descriptive research nature using document study data collection tools sourced from primary, secondary and tertiary legal materials, where the data are analyzed qualitatively. Keywords : Constitution, Omnibus Law, Concept.